1985
DOI: 10.1021/jf00065a017
|View full text |Cite
|
Sign up to set email alerts
|

Ethoxyquin, dihydroethoxyquin, and analogs as antinitrosamine agents for bacon

Abstract: Ethoxyquin, dihydroethoxyquin, and their analogues are potent inhibitors of nitrosamine formation in bacon even at levels as low as 20 ppm. As exemplified by ethoxyquin in the case of nitrosopyrrolidine, they function by competing with proline for the available nitrosating species to form initially 1nitrosoethoxyquin which rearranges to the 8-nitroso compound prior to oxidation by air to 8-nitroethoxyquin. The latter compound was isolated from ethoxyquin-treated bacons and also from the nitrosation of ethoxyqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

1986
1986
2014
2014

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 3 publications
0
10
0
Order By: Relevance
“…Ethoxyquin has been studied as an anti-nitrosamine agent for bacon. The mode of action for ethoxyquin has been reported in a few publications (Bharucha et al, 1985;Bharucha, 1987).…”
Section: Evaluation Of Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ethoxyquin has been studied as an anti-nitrosamine agent for bacon. The mode of action for ethoxyquin has been reported in a few publications (Bharucha et al, 1985;Bharucha, 1987).…”
Section: Evaluation Of Inhibitorsmentioning
confidence: 99%
“…Here, six inhibitors including glucose, vanillin, α-tocopherol, ascorbic acid, isoascorbic acid, and ethoxyquin with 5 mM concentration were screened for the first time for their inhibition activity towards nitrosamine formation in 5 M morpholine solution under utility operating conditions. These inhibitors have been previously studied under acidic conditions with one or the other amine towards their nitrosation activity (Bartsch et al, 1993;Bharucha et al, 1985;Bharucha et al, 1987;Perez et al, 1990;Tannenbaum et al, 1991). In the field of biologic and biomedical studies, nitrosation of morpholine in the presence of ascorbic acid has been reported by Perez et al during mutagenic activity in mice under low pH conditions (Perez et al, 1990).…”
Section: Evaluation Of Inhibitorsmentioning
confidence: 99%
“…After 6 h in dichloromethane the IV-nitroso content had dropped to 100%. Gas chromatography of the reaction mixture showed three peaks reminiscent of crude nitrosated ethoxyquin, but the retention times were very long under the conditions described previously (Bharucha et al, 1985). The oven temperature program was changed so that the oven was initially set at 170 °C with the injection port at 210 °C.…”
Section: Preparation Of Aromatic Primary and Secondarymentioning
confidence: 99%
“…On the basis of the proposed mechanism of action of ethoxyquin, dihydroethoxyquin, and their analogues in inhibiting nitrosamine formation in bacon, described in an earlier paper (Bharucha et al, 1985), it was postulated that aromatic amines, both primary and secondary, possessing an alkoxy substituent in the para position would behave similarly. Several of these anilines were synthesized and tested in bacon.…”
Section: Introductionmentioning
confidence: 99%
“…Except for astaxanthin, there are still some other active ingredients in Haematococcus pluvialis. Owing to their difficult separation and purification, few active ingredients have been obtained from Haematococcus pluvialis.The nitrification mechanism of ethoxyquinoline (EQ), photolysis of 8-nitro-EQ, and the antioxidant function of EQ in food additives have been studied [8][9][10][11][12], and the mass spectrometry data of some EQ metabolites from the post-harvest treatment of pears and apples have been reported [13]. However, no reports on the EQ-dimer (1) and 8-nitro-EQ (2) from Haematococcus pluvialis have been found in previous references.…”
mentioning
confidence: 99%